ინოვაციური ტენდენციები ოციანი წლების ბერძენი პოეტების შემოქმედებაში - ცინცაძე, ქეთევან (ლოგოსი, 2023)
Greek poets of 1920s put an end to the long-term process of the organic implementation of europian trends in Greek poetry. But its not the only contribution of them to the Greek literature, Neoromanticist-Neosymbolist poets also acted as reformators of Greek poem by adding for the further development vitaly important innovations to it. They were innovative in several directions; In the works of the poets of 1920s phonetics, stylistics, composition and ideology have undergone significant changes. In terms of phonetical changes inspired by the French Symbolist poets Greek Neoromanticist-Neosymbolist poets recognized musicality of poetry and paid special attention to the melody. As for the composition, innovation was bringing of lyrical verse. Neoromanticist-Neosymbolist poets rejected the elements of narrative poetry and began to compose short, emotionally inspired verses with no longer uninnterupted narrative line. At the same time they broke the traditional understanding of the strophe and gave a great extent to imagination. In 1920s significant changes were obtained in the ideology and stylistic of the moderns Greek poem. The Greek poets of the 1920s finally released the Greek poetry from the unrealistic Dream of „Megali Idea", set an end to the illusions and gave new directions to its’s ideology. In terms of stylistic poets of 1920s changed the linguistic and grammatical orientation of poetry. They refused dimoticism and replaced it with modern urban vocabulary enriched with lots of foreign terms. They also changed grammatical persons in poem. If the previous generation of poets, who had Gnostic relations to different things, always used plural for speaking about common matters, the poets of 1920s find topics of inspiration in their empirical experience, which resulted in changing of grammatical person to singular „I“.